Geological and Geomorphological Evaluation of Melendiz Stream Basin - Halil Mesut Baylak; Recep Bozyiğit (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2018)
The research area is the Melendiz Stream Basin in Aksaray. Melendiz Stream Basin is located in the Lake Tuz Closed Endorheic Basin. The Ihlara Valley part of the basin is included in the Cappadocia tourism zone. Paleozoic, Mesozoic, Tertiary and Quaternary formations are observed in the study area and its immediate surroundings. Mount Hasan, Melendiz Mountain, Mount Keçiboyduran, Mount Göllü and Mount Kulaklı volcanoes have been influential on these formations. Major morphological elements that draw attention are mountainous and hilly areas, piedmont plains that we see in the east of the Çiftlik district and Ihlara Canyon Valley. The Fairy Chimneys, the horizontal forms of the formations terrace sets , the covert appearance of the Mount Hasan ash, the thin but widespread outcrop of the travertines along the fault lines, constituted the present geomorphological structure of the erosion research area whose effects are observed. Göğüs Stream which is the largest tributary of Melendiz Stream forms the main stream of the basin. The Stream drains an area of approximately 565.2 km2 that we have identified with all of its tributaries. In Melendiz Stream, dendritic drenage is observed in the areas where the lateral tributaries reunite; braided drenage is observed along main stream flow area. The most important lake in the surrounding of research area is Mamasun Dam Lake.